Analisis Penegakan Hukum Terkait Tindak Pidana Illegal Logging di Kawasan Taman Nasional Indonesia dan Upaya Penanggulangannya - Silva Samantauli Lumban Gaol; Diah Ratna Sari Hariyanto (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this writing is to find out the legal regulations governing criminal acts of illegal logging that occur in the Indonesian National Park area and the efforts implemented by the government to overcome the impacts of illegal logging. This research uses normative law research methods, which involve analysis of library materials and legislation related to illegal logging. The results of the study show that the regulations of Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction are often used in enforcing illegal logging laws today. This law is an implementing regulation of Law Number 41 of 1999 concerning Forestry, which confirms that criminal acts of forest destruction remain valid as long as they do not conflict with Law Number 18 of 2013. The government is taking step preventive, monitoring, and repressive measures to tackle the criminal act of illegal logging.